1998
DOI: 10.1103/physrevb.58.9312
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of end-chain spin effects in the Haldane-gap materialNi(C3H10

Abstract: Electron spin resonance ͑ESR͒, at 9, 94, and 190 GHz, and magnetization studies on polycrystalline, powder, and ultrafine powder samples of Ni(C 3 H 10 N 2 ) 2 N 3 (ClO 4 ) ͑NINAZ͒ have revealed several effects arising from the Haldane phase. Using the g value of the end-chain spin S as determined by ESR, our results confirm that the end-chain spins are Sϭ 1 2 and show no evidence for Sϭ1 end-chains. In addition, the ESR signals reveal spectral weight consistent with a model describing interactions between the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In the cases where very high sensitivity is not requested the single-pass approach is applicable and a number of successful examples are found in literature in which this technique gives valuable insights into a variety of physical systems [13,[16][17][18][19][20][21][22][23][24][25][26]. With this technique it is possible to detect the number of spins which is generally higher than 10 12 spin/mT and seldom one order of magnitude lower.…”
Section: Introductionmentioning
confidence: 98%
“…In the cases where very high sensitivity is not requested the single-pass approach is applicable and a number of successful examples are found in literature in which this technique gives valuable insights into a variety of physical systems [13,[16][17][18][19][20][21][22][23][24][25][26]. With this technique it is possible to detect the number of spins which is generally higher than 10 12 spin/mT and seldom one order of magnitude lower.…”
Section: Introductionmentioning
confidence: 98%
“…Doping of PbNi2V20 s could be realized by a partial replacement of Ni 2 § (S = 1) with Mg 2+ (S = 0) resulting in a PbNi2_xMgxV20 s. On the basis of the valence-bond picture [6] it is known for a long time that the introduction of nonmagnetic impurities into the Haldane chain releases two S = 1/2 spins on each side of the impurity [7,8]. These spins have been indeed detected in PbNi2_xMgxV20 s by earlier electron spin resonance (ESR) measurements [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Again by means of numerical calculations, such as Monte Carlo [4] and density matrix renormalization group [5][6][7], it has been shown that in chains with a finite number of spins a staggered magnetization, exponentially decaying from the boundaries, should be induced by a homogeneous magnetic field. Evidence of these boundary effects have been achieved by electron spin resonance (ESR) spectra [8][9][10]. The resolution in these experiments, however, was not large enough to allow an identification of the local magnetization (Sf) pertaining to different chain sites i.…”
Section: Introductionmentioning
confidence: 99%